Synthesis of two isomers of 3-amino-7α-12α-dihydroxy-5β-cholanic acid - D. O. Barsuk; S. M. Kovalenko (Zaporozhye State Medical University, 2015)
Aim.With the aim of differences investigation in physical-chemical properties optimized synthesis of the two stereoisomers of 3-amino-7-12-dihydroxycholanic acid has been performed. Methods and results.As the source compound natural cholic acid was used. 3α-amino-7α-12α-dihydroxy-5β-cholanic acid was obtained in high yield and low number of by-products. The yield of 3β-amino-7α-12α-dihydroxy-5β-cholanic acid was low because of steric interference and process needed additional treatment stages. Column chromatography was used for cleaning compounds. The structure was studied and confirmed by NMR method. Significant differences in signals of NMR spectra and physical-chemical properties 3β-amino-7α-12α-dihydroxy-5β-cholanic acid and 3α-amino-7α-12α-dihydroxy-5β-cholanic acid wasn't found or observed.